Evaluation of the precision and accuracy of laboratory equipment that determines the quality of ovine fibres - Rubio Cieza, Mirian Yuliza (2020)
The study aimed to evaluate the precision and accuracy of equipment that determine the quality of sheep fibres. The equipment used (total = 15) were Sirolan Laserscan, OFDA 2000, Minifiber EC and Fiber EC, belonging to nine laboratories in Peru (n=7) and Argentina (n=2). The mean values of the mean diameter fibre (MDF) were determined in relation to the tolerance limits given by IWTO 12 and IWTO 47, using samples of fibres with known diameters. The accuracy was determined from the average obtained from the subsamples minus the actual value of the samples and the precision was evaluated by the standard deviation of the repetitions. Dunnett's multiple comparisons method was used for precision and accuracy. The results showed that the equipment coded as B and C in laboratories 4 and 8 were the most accurate, while equipment B and D in laboratories 5 and 8 shoed the highest precision. Six of the nine laboratories had equipment that determined the MDF within the tolerance limits given by IWTO 12 and IWTO 47. It is recommended to implement inter-laboratory and instrument tests that evaluate fibres at a national level.